ANALISIS KEMAMPUAN MENYUSUN BAHAN AJAR MENGGUNAKAN APLIKASI CANVA PADA MAHASISWA PROGRAM STUDI S1 PGSD - halidjah, siti (STKIP Melawi, 2024)
Abstract: The purpose of this study is to describe the ability to compile teaching materials using the Canva application in students of the S1 PGSD Study Program. The subject of the study is a student of the 2021 micro learning group. The data source is in the form of teaching materials documents prepared by students. The research process begins with the planning stage, implementation, followed by data analysis, and ends with reporting. The data collection technique uses document studies with the collection tool in the form of teaching material documents prepared by students. Data analysis follows the flow of collection, reduction, presentation, and conclusion. The results of the study showed that students' ability to compile teaching materials using the Canva application was in the